Scientific opinion on the renewal of the authorisation of proFagus Smoke R714 (SF‐001) as a smoke flavouring Primary Product - EFSA Panel name on Food Additives and Flavourings (FAF); Maged Younes; Gabriele Aquilina; Laurence Castle; Gisela Degen; Karl‐Heinz Engel; Paul J Fowler; Maria Jose Frutos Fernandez; Peter Fürst; Ursula Gundert‐Remy; Rainer Gürtler; Trine Husøy; et al. (EFSA Journal, 2023)
Abstract The EFSA Panel on Food Additives and Flavourings (FAF) was requested to evaluate the safety of the smoke flavouring Primary Product proFagus Smoke R714 (SF‐001), for which a renewal application was submitted in accordance with Article 12(1) of Regulation (EC) No 2065/2003. This opinion refers to the assessment of data submitted on chemical characterisation, dietary exposure and genotoxicity of the Primary Product. ProFagus Smoke R714 is obtained by pyrolysis of beech and oak woods as main source materials. Based on the compositional data, the Panel noted that the identified and quantified proportion of the solvent‐free fraction amounts to 39 weight (wt)%, thus the applied method does not meet the legal quality criterion that at least 50% of the solvent‐free fraction shall be identified and quantified. At the maximum proposed use levels, dietary exposure estimates calculated with DietEx ranged from 0.7 to 10.9 mg/kg body weight (bw) per day at the mean and from 2.2 to 42.5 mg/kg bw per day at the 95th percentile. The Panel concluded that three components in the Primary Product raise a potential concern for genotoxicity. In addition, a potential concern for genotoxicity was identified for the unidentified part of the mixture. The Primary Product contains furan‐2(5H)‐one, for which a concern for genotoxicity was identified in vivo upon oral administration. Considering that the exposure estimates for this component are above the threshold of toxicological concern (TTC) of 0.0025 μg/kg bw per day for DNA‐reactive mutagens and/or carcinogens, the Panel concluded that the Primary Product raises concern with respect to genotoxicity.